Gest??o de stakeholders em projetos com caracter??sticas socioambientais - Alencar, L??via Mac??do de (2019)
This dissertation seeks to enrich the content of the project management sustainability thinking school, and its scientific community, by analyzing the management of stakeholders within a unique case study. The railway infrastructure project Line 13 - Jade, which connects the cities of S??o Paulo and Guarulhos, was used as the unit of analysis, in which the actions to implement the socio-environmental elements of the project were observed. Therefore, this research is problematized around the search for techniques and practices that connect knowledge towards the current paradigmatic change of sustainable development and advances in stakeholder management. This is a qualitative research that analyzed six interviews with key project members, as well as public documents and journalistic reports. In this research, the identification of how stakeholders act in relation to the project, whether affecting the project and / or being affected by it, was represented by classification diagrams, which enabled the analysis of interrelationships and their impacts on the project, considering the existing social and environmental context, which was represented through the linkage matrix. The presence of the stakeholder management approach was identified and it was noted that the role of stakeholder management requires proactive action to engage external stakeholders with lesser power and balance the financial, social and environmental dimensions. Practical contributions of the research are the indication of the creation of a social and environmental space that served as the interface between the project and the population; the creation of an opinion polling system for engagement and participation of external stakeholders in decision making; the application of specific contract templates; the hire of project managers interested in working to meet social and environmental elements. It is suggested that the project management best practice guides include consideration of environmental interests in stakeholder management. As academic contributions, this research identifies two scientific gaps that may constitute a research agenda: one related to the review of the concept of stakeholders, which may lead to a scientific innovation; and another relates to the participative management of stakeholders, assessing the interference in decision making.